Relationship between Total Length and Digestive Tract of Different Carnivorous Fishes - Rahman, MM; Alam, MMM; Zaman, T (Progressive Agriculture, 2013)
The study was conducted to find out the relationship between total length and alimentary canal of different carnivorous fishes. The morphometry associated with the feeding and digestion of one hundred eighty fishes of 9 species was studied. It was observed that well-defined sharp teeth were present on both jawsof the fishes examined. It was also found that the fishes had rough surface pharyngeal pads. The total length of Johnius koitor, Channa orientalis, Channapunctatus, Mvstus vittatus, Glossogobius giuris, Nandus nandus, Eleotris fusca and Anabas testudineus were 1.28 to 1.72, 2.90 to 3.17, 2.22 to 2.70, 2.00 to 2.40, 3.00 to4.50, 1.20 to 1.50, 1.40 to 2.36 and 1.48 to 1.64 times greater than the intestinal length, respectively and the intestinal lengths were 5.45 to 6.02, 1.30 to 1.70, 1.70 to 2.10, 3.60 to 4.10, 2.10 to 2.50, 2.90 to 3.20, 2.00 to 12.00 and 3.00 to 5.30 times longer than the stomach of the fishes, respectively. The total length of Xenontodon cancila was 9.20 to 9.80 times greater than the intestinal length and the stomach length was 1.90 to 2.20 times greater than the intestinal length with an average of 2.00 times. DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16564 Progress. Agric. 23(1 & 2): 39 49, 2012